Is excision biopsy of fibroadenomas based solely on size criteria warranted? - Neville, Grace; Neill, Cathleen O'; Murphy, Rosemary; Corrigan, Mark; Redmond, Paul H.; Feeley, Linda; Bennett, Michael W.; O'Connell, Fionnuala; Browne, Tara Jane (Breast Journal)
Fibroadenomas (FA) are the most common benign tumor in the female breast. Most are managed conservatively provided there is clinical, radiologic, and pathologic concordance. However, surgical excision is typically recommended for cellular fibroepithelial lesions or those lesions with clinical, radiologic, or pathologic features concerning for phyllodes tumor (PT). Some studies have suggested surgical excision in all FA >30 mm to reduce core needle biopsy (CNB) sampling errors. The aim of our study was to evaluate, in the absence of any other concerning clinicopathologic features, whether surgical excision of FA was warranted based on size criteria alone. Cork University Hospital is a large academic center in Southern Ireland. Its breast cancer center provides both a screening and symptomatic service and diagnoses approximately 600 cancers per year. The breast histopathological data base was reviewed for all CNBs from January 1, 2010, to June 30, 2015, with a diagnosis of FA that went on to have excision at our institution. We excluded all cellular fibroepithelial lesions and those cases with co‐existent lobular neoplasia, ductal carcinoma in situ, invasive carcinoma, atypical ductal hyperplasia, or lesions which would require excision in their own right. Cases in which the radiologic targeted mass was discordant with a diagnosis of FA were also excluded. Patient demographics and preoperative radiologic size and the radiologic target were recorded in each case. All radiology was reviewed by a breast radiologist prior to inclusion in the study, and there was histologic radiologic concordance with a diagnosis of FA in all cases. A total of 12,109 consecutive radiologically guided CNB were performed January 2010‐June 2015; 3438 with a diagnosis of FA were identified of which 290 cases went on to have surgical excision. Of those 290 cases; 98.28% (n = 285) were confirmed as FA on excision. The remaining 1.72% (n = 5) had atypical features—FA with LCIS (n = 1), benign PT (n = 3), and invasive ductal carcinoma (n = 1). Our study suggests that, excision based solely on size is not warranted in clinical and radiologically concordant cases with a diagnosis of FA on CNB.